Au nanoparticle-coated, PLGA-based hybrid capsules for combined ultrasound imaging and HIFU therapy1. Issue 20 (28th May 2015) - Xi, Juqun; Qian, Xiaodong; Qian, Kehong; Zhang, Wanying; He, Wen; Chen, Yan; Han, Jie; Zhang, YuZhen; Yang, XiangJun; Fan, Lei
<x xml:space="preserve">Abstract</x> A simple method to prepare AuNPs@PDA/PLGA hybrid capsules for combined ultrasound imaging and HIFU therapy was presented.